Exploring factors that influence the behavior response to novel object tests in young thoroughbred horses: investigating sex, test site and auction history - Klitzing, Lara; Kirsch, Katharina; Schindler, Maria; Merle, Roswitha; Hoffmann, Gundula; Thöne-Reineke, Christa; Wiegard, Mechthild (Frontiers in Veterinary Science, 2025)
IntroductionThe novel object test is one of the three most common fear tests in veterinary science and employed in several different species. Although having been applied in several different studies in horses, it is surprising that there is no standardized test procedure available for these kinds of tests.MethodsThis study investigated the performance of the novel object test on 42 young Thoroughbred horses to determine the effect of sex (mare or stallion), test sites (round pen or paddock) and whether the horses had previously participated in an auction or not on the behavior during the novel object test.ResultsDifferences in horses’ behavior during the novel object test were primarily attributed to the test sites. The animals showed significant (p < 0.05) intra-individual differences in the novel object test in the round pen and in the paddock. Sex did not affect the direct interaction with the novel object. The horses that had not participated in an auction seemed to actively perceive the novel object more quickly, so that the latency to first fixation on the object was significantly shorter.DiscussionIn order to obtain comparable results, it is recommended that novel object tests should be performed at the same location and under identical conditions. Furthermore, it is important to consider the individual behavior of each horse.